Microgreens: Production, shelf life, and bioactive components. Issue 12 (13th August 2017) - Mir, Shabir Ahmad; Shah, Manzoor Ahmad; Mir, Mohammad Maqbool
ABSTRACT: Microgreens are emerging specialty food products which are gaining popularity and increased attention nowadays. They are young and tender cotyledonary leafy greens that are found in a pleasing palette of colors, textures, and flavors. Microgreens are a new class of edible vegetables harvested when first leaves have fully expanded and before true leaves have emerged. They are gaining popularity as a new culinary ingredient. They are used to enhance salads or as edible garnishes to embellish a wide variety of other dishes. Common microgreens are grown mainly from mustard, cabbage, radish, buckwheat, lettuce, spinach, etc. The consumption of microgreens has nowadays increased due to higher concentrations of bioactive components such as vitamins, minerals, and antioxidants than mature greens, which are important for human health. However, they typically have a short shelf life due to rapid product deterioration. This review aimed to evaluate the postharvest quality, potential bioactive compounds, and shelf life of microgreens for proper management of this specialty produce.